The Effect of Aerobic Exercise and Vinyasa Yoga on Body Fat Reduction among Women Gym Members at G Sports Center in Padang City - Chinta, Ira; Handayani, Sri Gustri; Ihsan, Nurul; Khairuddin, Khairuddin; Ockta, Yovhandra (Poltekita : Jurnal Ilmu Kesehatan, 2024)
Adult female exercise members who take part in activities at the G Sports Center still do not know the exercises that are effective in reducing fat in their bodies. The purpose of this study is to determine the significant difference in influence between the aerobic mix impact exercise method and whether vinyasa yoga has a significant effect on reducing body fat in female exercise members at the G Sports Center. This research is a quasi-experimental study. With a study design of two pretest-postest groups. The population in this study was female exercise members with an age range of 19 to 45 years with a total of 30 women while the sampling technique in this study used a saturated census/sampling technique. So that the entire population was involved in this study. Data were obtained using an observation sheet by measuring fat using the Omron HBF 375 BIA Tool. This tool can be used in a flat place, resulting in accurate data. Data were analyzed descriptively using a t-test with a significant level of α = 0.05. The results showed that there was an effect of mixed-impact aerobic exercise on body fat reduction (p = 0.000) and there was an effect of vinyasa yoga practice on body fat reduction (p = 0.000). There was a significant difference between mixed-impact aerobic exercise and vinyasa yoga practice on fat reduction (p = 0.041). From both treatments, mixed-impact aerobic exercise had a greater effect on fat reduction with an average body fat pretest of 31,727 and posttest 27,653 with a difference in average scores. -The average was 4,074. So aerobic mix impact exercise is recommended for someone, especially in women if you want to reduce body fat.